Partizipation als Forschungsmodus: Aus der Praxis des teilnehmenden Beobachtens - Beuchling, Olaf (International Dialogues on Education Journal, 2015)
The following article deals with participant observation, a social-science method that, in spite of its long tradition, still has a high exploratory, documentary, and theoretical potential. Participant observation is a social-science procedure in which the researchers participate in the everyday life of the people who are the focus of the investigation, in order to answer questions pertaining to their lived reality based on intimate knowledge. The article claims that this method is particularly suitable for discovering the heterogeneous life conditions and experiential realms of children, youth, families, and pedagogical institutions. The paper, which is oriented towards research praxis, discusses the history of participant observation, relevant application areas, procedures, challenges, as well as instructions for writing field notes.